3 D Porous CoS2 Hexadecahedron Derived from MOC toward Ultrafast and Long‐Lifespan Lithium Storage. Issue 26 (20th April 2018) - Wang, Han‐Chi; Cui, Zheng; Fan, Chao‐Ying; Liu, Si‐Yu; Shi, Yan‐Hong; Wu, Xing‐Long; Zhang, Jing‐Ping
Abstract: A new hexadecahedron assembled by core–shell CoS2 particles@N‐doped carbon (CoS2 @NCH) is prepared successfully through the self‐templating method. The CoS2 @NCH hybrid electrode delivers a high lithium‐storage capacity of 778 mA h g −1 after 1000 cycles at a high current density of 1 A g −1, which is the longest cycle lifespan among the reported CoS2 anode materials in lithium‐ion batteries. Furthermore, the CoS2 @NCH hybrid electrode shows excellent rate capability with a discharge capacity of 220 mA h g −1 at an extremely high current density of 20 A g −1, and a charge capacity of 649 mA h g −1 is restored upon returning the current density back to 2 A g −1 . The superior performance is attributed to the unique construction of CoS2 @NCH. The N‐doped interconnected porous carbon shells form highly conductive skeletons for quick electron transfer and prevent the electrode from collapsing. Moreover, the porous characteristic of the materials plays a key role: as some effective channels, the mesopores on the porous carbon shells provide greater access for lithium, and the mesopores derived from the particle interspace enables the complete immersion of the electrodes in electrolyte, which alleviates the volume expansion and ensures the integrity of the electrode. In addition, the nanosized CoS2 particles, which shorten the ion‐transport path and provide extra electroactive sites, also improve the reaction kinetics. Abstract : Hexadecahedron anode : The obtained new CoS2 @NCH anode material displays excellent long‐lifespan properties, with a capacity as high as 780 mA h g −1 after 1000 cycles at a current density of 1 A g −1 (see figure). Upon increasing the current density to 20 A g −1, the charge capacity remains as high as 220 mA h g −1 .